Terminal film for power storage device and power storage device using same
By using a terminal film composed of polypropylene and polyethylene to cover the metal terminals of the lithium-ion secondary battery, the safety problems caused by electrolyte leakage are solved, and higher safety and performance stability are achieved.
Patent Information
- Application Number
- CN202380043559.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-06-05
- Publication Date
- 2025-02-07
AI Technical Summary
Lithium-ion secondary batteries have a risk of fire due to the use of combustible materials, especially the problem of leakage of electrolyte when it falls, causing corrosion of peripheral components.
A terminal film including polypropylene and polyethylene is provided for covering the outer peripheral surface of the metal terminal, and through excellent adhesion and sealing properties, leakage of the electrolyte upon drop is suppressed.
It effectively improves the safety of the power storage device, prevents the leakage of electrolyte during drop, and reduces the risk of performance losses.
Smart Images

Figure CN119404355A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a terminal film for a power storage device and a power storage device using the terminal film for a power storage device. Background Art
[0002] In recent years, demands for miniaturization of portable devices and effective use of natural power generation have increased, and research and development of lithium-ion secondary batteries (a type of power storage device) that can achieve higher voltage and higher energy density have been underway.
[0003] As the packaging material used in the above-mentioned lithium-ion secondary batteries, metal cans have been mostly used in the past. However, in view of the requirements for thinning and diversification of applicable products, for the reason of low manufacturing cost, a packaging material obtained by laminating a metal layer (such as aluminum foil) and a resin film in a bag shape is mostly used.
[0004] The laminated lithium-ion secondary battery in which the battery body is sealed inside the above-mentioned packaging material has a current output terminal called a tab. The tab has a metal terminal (sometimes also called a "tab lead") connected to the negative electrode or positive electrode of the battery body and extending to the outside of the packaging material (packaging material) and a terminal film (sometimes also called a "tab sealant") that covers a portion of the outer peripheral surface of the metal terminal. Usually, the terminal film is welded to the metal terminal (for example, Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-008803 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, lithium-ion secondary batteries require high safety. However, lithium-ion secondary batteries use flammable materials, and sometimes fire becomes a problem. Fire is caused, for example, when a lithium-ion secondary battery is dropped, electrolyte leaks and the electrolyte causes corrosion of surrounding parts.
[0010] The adhesive film for a metal terminal disclosed in Patent Document 1 has room for improvement in terms of safety when it is dropped.
[0011] The present disclosure has been made in view of the above-mentioned problems of the prior art, and provides a terminal film capable of suppressing the occurrence of electrolyte leakage when dropped and improving the safety of a power storage device, and a power storage device using the terminal film.
[0012] Means for solving problems
[0013] One aspect of the present disclosure is a terminal film for a power storage device for covering a portion of an outer peripheral surface of a metal terminal constituting a power storage device, the terminal film comprising polypropylene and polyethylene, the terminal film having a first surface satisfying the following formula (A1).
[0014] 0.3≤a2 / a1≤6.2(A1)
[0015] [In formula (A1), a1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of a2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0016] The first surface of the terminal film satisfies the above formula (A1). As a result, the terminal film has excellent adhesion to the packaging material and exhibits good sealing properties. As a result, the terminal film can suppress the occurrence of electrolyte leakage when dropped, thereby improving the safety of the power storage device. In addition, the above-mentioned terminal film tends to be able to suppress the degradation of performance caused by electrolyte leakage when dropped.
[0017] Another aspect of the present disclosure is a terminal film for a storage device, which is used to cover a portion of the outer peripheral surface of a metal terminal constituting the storage device, and comprises: a first resin layer containing polypropylene and polyethylene, a second resin layer containing polypropylene, and an intermediate layer arranged between the first resin layer and the second resin layer and containing polypropylene, the first resin layer having a first surface satisfying the following formula (A1) as one surface of the terminal resin film.
[0018] 0.3≤a2 / a1≤6.2(A1)
[0019] [In formula (A1), a1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of a2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0020] The first surface of the terminal film satisfies the above formula (A1). As a result, the terminal film has excellent adhesion to the packaging material and exhibits good sealing properties. As a result, the terminal film can suppress the occurrence of electrolyte leakage when dropped, thereby improving the safety of the power storage device.
[0021] In one embodiment, the intermediate layer may satisfy the following formula (B1): Thus, the terminal film tends to have better safety.
[0022] 1.0≤b2 / b1≤3.2(B1)
[0023] [In formula (B1), b1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of b2 is 841 cm when measured by attenuated total reflection method of infrared spectroscopy. -1 The absorption intensity.]
[0024] In one embodiment, the second resin layer may satisfy the following formula (C1): Thereby, the safety of the terminal film tends to be further improved.
[0025] 1.0≤c2 / c1≤5.8(C1)
[0026] [In formula (C1), c1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of C2 is the wave number 841 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0027] In one embodiment, the terminal film may include a compatibilizer having a portion compatible with polypropylene and a portion compatible with polyethylene. Thus, the terminal film tends to be able to improve adhesion with a sealing layer of a packaging material.
[0028] In one embodiment, the compatibilizer may be a block copolymer or a graft copolymer, which tends to enhance the compatibilizing effect.
[0029] Another aspect of the present disclosure is a power storage device comprising: a power storage device body, a metal terminal electrically connected to the power storage device body, a packaging material that clamps the metal terminal and accommodates the power storage device body, and the above-mentioned terminal film for the power storage device that covers a portion of the outer peripheral surface of the metal terminal and is arranged between the metal terminal and the packaging material, the packaging material having a sealing layer containing polypropylene, the terminal film being arranged in such a way that the first surface is in contact with the sealing layer, and the sealing layer satisfies the following formula (D1).
[0030] 0.8≤d2 / d1≤8.5(D1)
[0031] [In formula (D1), d1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of d2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0032] Effects of the Invention
[0033] According to the present disclosure, there are provided a terminal film for an electric storage device capable of suppressing the occurrence of electrolyte leakage when dropped and improving the safety of the electric storage device, and an electric storage device using the terminal film for an electric storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] [ Figure 1 ] is a perspective view showing the schematic structure of the power storage device involved in an embodiment of the present disclosure.
[0035] [ Figure 2 ] to show Figure 1 A cross-sectional view showing an example of a cut surface of a packaging material shown.
[0036] [ Figure 3 ]for Figure 1 The cross-sectional view of the terminal film and the metal terminal along the AA line is shown. DETAILED DESCRIPTION
[0037] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. It should be noted that in the accompanying drawings, the same symbols are marked for the same or corresponding parts, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.
[0038] Figure 1 1 is a perspective view showing a schematic configuration of a power storage device according to an embodiment of the present disclosure. Figure 1 In the embodiment, a lithium ion secondary battery is listed and illustrated as an example of the power storage device 10, and the following description is given. Figure 1 The lithium ion secondary battery having the structure shown is sometimes referred to as a battery pack, a battery cell, or the like.
[0039] Figure 1 The power storage device 10 shown is a lithium ion secondary battery having a power storage device body 11 , a packaging material 13 , a pair of metal terminals 14 (tab leads), and a power storage device terminal film 16 (tab seal, hereinafter also simply referred to as “terminal film 16 ”).
[0040] The power storage device body 11 is a battery body that performs charge and discharge. The exterior material 13 is disposed so as to cover the surface of the power storage device body 11 and to be in contact with a part of the terminal film 16 .
[0041] Figure 2 To show Figure 1 An example of a cross-sectional view of a cut surface of a packaging material is shown. Figure 2 In, with Figure 1 The same components of the structures shown are denoted by the same reference numerals.
[0042] Here, refer to Figure 2, an example of the composition of the packaging material 13 is described. The packaging material 13 has a seven-layer structure in which an inner layer 21, an inner layer side adhesive layer 22, an anti-corrosion treatment layer 23-1, a barrier layer 24 as a metal layer, an anti-corrosion treatment layer 23-2, an outer layer side adhesive layer 25, and an outer layer 26 are stacked in order from the inner side in contact with the storage device body 11.
[0043] The inner layer 21 is a sealing layer that imparts heat-seal sealing properties to the packaging material 13, and is a layer that is arranged on the inner side and is heat-sealed (heat-fused) when the power storage device 10 is assembled. As the base material of the inner layer (sealing layer) 21, for example, polyolefin resins and acid-modified polyolefin resins obtained by grafting and modifying polyolefin resins with maleic anhydride or the like can be used. As the above-mentioned polyolefin resin, for example, low-density, medium-density, and high-density polyethylenes; ethylene-α-olefin copolymers; homopolymers, block or random polypropylenes; propylene-α-olefin copolymers, etc. can be used. Among these, the above-mentioned polyolefin resin preferably contains polypropylene. These polyolefin resins can be used alone or in combination of two or more.
[0044] When the inner layer 21 contains polypropylene and polyethylene, the total content of polypropylene and polyethylene can be 50 mass% or more, 55 mass% or more, 60 mass% or more, or 65 mass% or less, based on the total amount of the inner layer 21, and can be 100 mass% or less, 90 mass% or less, 80 mass% or less, or 70 mass% or less.
[0045] The ratio of the mass of the (A) polypropylene to the total mass of the (A) polypropylene and the (B) polyethylene in the inner layer 21 can be appropriately changed so that the inner layer 21 satisfies the formula (D1) described later.
[0046] In order to suppress electrolyte leakage when dropped and further improve the safety of the power storage device, the inner layer 21 may satisfy the following formula (D1): In the formula (D1), from the same viewpoint, d2 / d1 is preferably 0.9 to 6.0, more preferably 1.0 to 3.0.
[0047] 0.8≤d2 / d1≤8.5(D1)
[0048] [In formula (D1), d1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of d2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0049] In addition, the inner layer 21 may be composed of a single layer film or a multilayer film having a plurality of layers stacked thereon, depending on the required functions. Specifically, for example, in order to impart moisture resistance, a multilayer film sandwiching a resin such as an ethylene-cyclic olefin copolymer or polymethylpentene may be used. In addition, the inner layer 21 may contain various additives (e.g., flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, tackifiers, etc.).
[0050] The thickness of the inner layer 21 is preferably set within a range of 10 to 150 μm, more preferably 30 to 80 μm. When the thickness of the inner layer 21 is thinner than 10 μm, the heat-sealing adhesion between the packaging materials 13 and the adhesion with the terminal film 16 may be reduced. In addition, when the thickness of the inner layer 21 is thicker than 150 μm, it becomes the main reason for the increase in the cost of the packaging material 13, so it is not preferred.
[0051] As the inner side adhesive layer 22, for example, a known adhesive such as a general dry lamination adhesive and an acid-modified hot-melt resin can be appropriately selected and used.
[0052] like Figure 2 As shown, the anti-corrosion treatment layers 23-1 and 23-2 are preferably formed on both sides of the barrier layer 24 in terms of performance, but considering the cost, the anti-corrosion treatment layer 23-1 can also be configured only on the surface of the barrier layer 24 located on the inner layer side adhesive layer 22 side.
[0053] The barrier layer 24 is, for example, a metal layer having conductivity. Examples of the material of the barrier layer 24 include aluminum and stainless steel, but aluminum is preferred from the viewpoint of cost, mass (density), and the like.
[0054] As the outer side adhesive layer 25, for example, a general polyurethane-based adhesive containing polyester polyol, polyether polyol, acrylic polyol or the like as a main component can be used.
[0055] As the outer layer 26, for example, a single layer film or a multilayer film of nylon, polyethylene terephthalate (PET), etc. can be used. As with the inner layer 21, the outer layer 26 can contain various additives (for example, flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, tackifiers, etc.). In addition, as a countermeasure for leakage, the outer layer 26 can have a protective layer formed by laminating a resin insoluble in the electrolyte or coating a resin component insoluble in the electrolyte.
[0056] Figure 3 yes Figure 1 The cross-sectional view of the terminal film and metal terminal along the AA line is shown. Figure 3 In, with Figure 1 The same components of the structures shown are denoted by the same reference numerals.
[0057] like Figure 1 and Figure 3 As shown, a pair ( Figure 1 The metal terminal 14 has a metal terminal body 14-1 and an anti-corrosion layer 14-2. One of the pair of metal terminal bodies 14-1 is electrically connected to the positive electrode of the power storage device body 11, and the other metal terminal body 14-1 is electrically connected to the negative electrode of the power storage device body 11. The pair of metal terminal bodies 14-1 extend in a direction away from the power storage device body 11, and a portion thereof is exposed from the packaging material 13. The shape of the pair of metal terminal bodies 14-1 can be, for example, a flat plate shape.
[0058] Metal can be used as the material of the metal terminal body 14 - 1 . The metal used as the material of the metal terminal body 14 - 1 is preferably determined in consideration of the structure of the power storage device body 11 , the material of each component of the power storage device body 11 , and the like.
[0059] For example, when the power storage device 10 is a lithium-ion secondary battery, aluminum is used as a collector for the positive electrode, and copper is used as a collector for the negative electrode. In this case, aluminum is preferably used as a material for the metal terminal body 14-1 connected to the positive electrode of the power storage device body 11. In addition, considering the corrosion resistance to the electrolyte, as a material for the metal terminal body 14-1 connected to the positive electrode of the power storage device body 11, for example, an aluminum material with a purity of 97% or more, such as 1N30, is suitable. In addition, in the case of bending the metal terminal body 14-1, in order to add flexibility, it is preferable to use an O material that has been tempered by sufficient annealing. As a material for the metal terminal body 14-1 connected to the negative electrode of the power storage device body 11, copper or nickel with a nickel plating layer formed on the surface is preferably used.
[0060] The thickness of the metal terminal body 14-1 depends on the size and capacity of the lithium-ion secondary battery. In the case of a small lithium-ion secondary battery, the thickness of the metal terminal body 14-1 can be, for example, 50 μm or more. In the case of a large lithium-ion secondary battery such as a storage battery or a vehicle-mounted battery, the thickness of the metal terminal body 14-1 can be appropriately set within a range of, for example, 100 to 500 μm.
[0061] The anti-corrosion layer 14-2 is configured to cover the surface of the metal terminal body 14-1. In the case of a lithium-ion secondary battery, the electrolyte contains corrosive components such as LiPF6. The anti-corrosion layer 14-2 is a layer for inhibiting the metal terminal body 14-1 from being corroded by the corrosive components such as LiPF6 contained in the electrolyte.
[0062] like Figure 3As shown, the terminal film 16 is configured to cover a portion of the outer peripheral surface of the metal terminal 14. In the present embodiment, the terminal film 16 has a structure consisting of a first resin layer 31 stacked in contact with the packaging material 13, a second resin layer 32 in contact with the outer peripheral side surface of the metal terminal 14, and an intermediate layer 33 arranged between the first resin layer 31 and the second resin layer 32.
[0063] The first resin layer 31 seals the inside of the sealing material 13 by being welded to the sealing material 13. The second resin layer 32 seals the circumference of the metal terminal 14 and makes the terminal film 16 and the metal terminal 14 closely attached by being arranged to cover the outer peripheral surface of the metal terminal 14.
[0064] In the present embodiment, the first resin layer 31 and the second resin layer 32 include (A) polypropylene (hereinafter also referred to as "(A) component") and (B) polyethylene (hereinafter also referred to as "(B) component"). As described later, the intermediate layer 33 includes polypropylene. That is, the terminal film 16 is a film made of a single material using the same material. Therefore, the terminal film 16 has excellent suitability for reuse.
[0065] The first resin layer 31 and the second resin layer 32 may further contain (C) a compatibilizer (hereinafter also referred to as “component C”) having a portion compatible with the (A) polypropylene and a portion compatible with the (B) polyethylene.
[0066] As the (A) polypropylene, homopolypropylene, random polypropylene, block polypropylene, etc. can be used. Among these, random polypropylene having a melting point of 110 to 150° C. is preferably used from the viewpoint of opening properties and impact resistance in a high temperature environment.
[0067] (A) Polypropylene may include modified polypropylene having a polar group. (A) Polypropylene can further improve the adhesion between the second resin layer 32 and the metal terminal 14 by having a polar group. As polar groups, for example, hydroxyl, glycidyl, amide, imino, oxazoline, anhydride, carboxyl, ester, etc. can be listed. From the viewpoint of reactivity, anhydride groups (especially groups derived from maleic anhydride) are preferred as polar groups. Modified polypropylene can be acid-modified polypropylene obtained by grafting maleic anhydride or the like. As specific product examples of modified polypropylene, for example, "Admer" manufactured by Mitsui Chemicals, Inc., "Modic" manufactured by Mitsubishi Chemical Corporation, "Toyo-Tac" manufactured by Toyobo Co., Ltd., "Umex Sanstac" manufactured by Sanyo Chemical Industries, Ltd., etc. can be listed. (A) Polypropylene can be used alone or in combination of two or more.
[0068] The melting point of the polypropylene (A) is preferably 110 to 165° C., more preferably 120 to 150° C. By setting the melting point of the polypropylene (A) to 165° C. or less, it is possible to suppress a decrease in the opening property under a high temperature environment, and by setting the melting point of the polypropylene (A) to 110° C. or more, it is possible to further improve the sealing strength at a temperature (e.g., 100° C.) lower than the target opening temperature (e.g., 130° C.), and the opening temperature can be appropriately controlled.
[0069] Examples of the polyethylene (B) include ultra-low density polyethylene (VLDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), and high density polyethylene (HDPE). Among these, LDPE and LLDPE are preferably used from the viewpoint of further improving heat sealability and heat seal strength.
[0070] (B) Polyethylene may include modified polyethylene having polar groups. (B) Polyethylene can further improve the adhesion between the second resin layer 32 and the metal terminal 14 by having polar groups. As polar groups, for example, hydroxyl, glycidyl, amide, imino, oxazoline, anhydride, carboxyl, ester, etc. can be listed. From the viewpoint of reactivity, anhydride groups (especially groups derived from maleic anhydride) are preferred as polar groups. Modified polyethylene can be acid-modified polyethylene obtained by grafting maleic anhydride or the like. As specific product examples of modified polyethylene, for example, "Admer" manufactured by Mitsui Chemicals, Inc. and "Modic" manufactured by Mitsubishi Chemical Corporation can be listed. (B) Polyethylene can be used alone or in combination of two or more.
[0071] The melting point of the polyethylene (B) is preferably 80 to 135° C., more preferably 100 to 125° C. When the melting point of the polyethylene (B) is 135° C. or lower, the opening property in a high temperature environment can be further improved, and when it is 80° C. or higher, opening during the production of the power storage device can be prevented.
[0072] In this specification, the melting point of a resin can be determined by measuring it using a differential scanning calorimeter (DSC), taking the top of a peak having the largest heat of fusion as a main peak, and reading the peak temperature.
[0073] The (C) compatibilizer has a portion compatible with the (A) polypropylene and a portion compatible with the (B) polyethylene. The (C) compatibilizer has the function of improving the adhesion between the second resin layer 32 and the packaging material 13. In addition, the (C) compatibilizer also has the function of improving the adhesion strength of the sea-island interface between the (A) polypropylene and the (B) polyethylene.
[0074] Examples of the compatibilizer (C) include ethylene-propylene rubber (EPR), ethylene-propylene-diene rubber (EPDM), a block copolymer having a portion compatible with (A) polypropylene and a portion compatible with (B) polyethylene, and a graft copolymer having a portion compatible with (A) polypropylene and a portion compatible with (B) polyethylene.
[0075] As the block copolymer, for example, there can be listed: a block copolymer composed of a crystalline polyethylene unit and an ethylene-butene copolymer unit, a block copolymer composed of a polyethylene unit and an ethylene-1-octene copolymer unit, a block copolymer composed of a polypropylene unit and a polyethylene unit, etc. In addition, as the graft copolymer, for example, there can be listed a graft copolymer obtained by grafting a polyethylene unit onto polypropylene, etc. Each unit constituting the copolymer can be a crystalline unit or a non-crystalline unit.
[0076] As the compatibilizer (C), a block copolymer or a graft copolymer is preferably used from the viewpoint of compatibility, and a compatibilizer having a non-crystalline unit is preferably used from the viewpoint of opening properties. The compatibilizer (C) may be used alone or in combination of two or more.
[0077] In the compatibilizer (C), the content ratio of the part compatible with (A) polypropylene and the part compatible with (B) polyethylene (mass ratio of the part compatible with (A) polypropylene / the part compatible with polyethylene) is preferably 1 / 9 to 9 / 1, more preferably 2 / 8 to 8 / 2, and further preferably 3 / 7 to 7 / 3. By making the content ratio greater than 1 / 9, the adhesion strength between the terminal film and the sealing layer of the packaging material can be further improved via the compatibilizer (C). On the other hand, by making the content ratio less than 9 / 1, the adhesion strength between the compatibilizer (C) and the polyethylene (B) can be further improved.
[0078] The first resin layer 31 and the second resin layer 32 may contain a resin having a polar group. Here, the resin having a polar group may be any one of the components (A) to (C), or may be a resin (D) having a polar group (hereinafter also referred to as a "polar resin") which is another component different from the components (A) to (C). When none of the components (A) to (C) have a polar group, it is effective to add the polar resin (D), but when one or more of the components (A) to (C) have a polar group, a polar resin (D) may be further added.
[0079] As the polar group contained in the (D) polar resin, for example, a hydroxyl group, a glycidyl group, an amide group, an imino group, an oxazoline group, an anhydride group, a carboxyl group, an ester group, etc. can be listed. From the viewpoint of reactivity, as the polar group, an anhydride group (particularly a group derived from maleic anhydride) is preferred. In addition, the (D) polar resin more preferably has a portion compatible with the (B) polyethylene portion.
[0080] There are no particular restrictions on the (D) polar resin other than the above-mentioned (A) to (C) components, and examples thereof include copolymers of olefins such as ethylene or propylene and other monomers copolymerizable with the olefins. For example, by using a monomer having a polar group as the other monomer, a resin having a polar group can be obtained. Examples of such (D) polar resins include ethylene / acrylic acid / glycidyl methacrylate copolymers, polyhydroxy polyolefin oligomers, and the like. The (D) polar resins may be used alone or in combination of two or more.
[0081] Based on the total amount of each layer, the total content of (A) polypropylene and (B) polyethylene can be 50% by mass or more, 60% by mass or more, 70% by mass or more, or 80% by mass or more, and can be 100% by mass or less, 97.5% by mass or less, 95% by mass or less, or 92.5% by mass or less.
[0082] The ratio of the mass of (A) polypropylene to the total mass of (A) polypropylene and (B) polyethylene in the first resin layer 31 can be appropriately changed so that the first resin layer 31 satisfies the formula (A1) described below. The ratio of the mass of (A) polypropylene to the total mass of (A) polypropylene and (B) polyethylene in the second resin layer 32 can be appropriately changed so that the second resin layer 32 satisfies the formula (C1) described below.
[0083] The ratio of the mass of the (C) compatibilizer to the total mass of the (A) to (C) components in the first resin layer 31 can be appropriately changed so that the first resin layer 31 satisfies the formula (A1) described below. The ratio of the mass of the (C) compatibilizer to the total mass of the (A) to (C) components in the second resin layer 32 can be appropriately changed so that the second resin layer 32 satisfies the formula (C1) described below.
[0084] When the first resin layer 31 and / or the second resin layer 32 contain (D) polar resin, the content thereof is preferably 1 to 20% by mass, more preferably 5 to 15% by mass, based on the total amount of each layer. When the content of (D) polar resin is 1% by mass or more, the adhesion with the metal terminal at room temperature tends to be further improved, and when it is 20% by mass or less, it tends to be easy to suppress the opening property at high temperature and the decrease in the adhesion with the packaging material at room temperature.
[0085] In the first resin layer 31 and the second resin layer 32, when one or more of the above-mentioned components (A) to (C) is a resin having a polar group, from the viewpoint of further improving the adhesion with the metal terminal under room temperature, the proportion of the resin having a polar group in the total amount of components (A) to (C) is preferably 40% by mass or more, and more preferably 80% by mass or more.
[0086] Additives other than the above components may be added to the first resin layer 31 and the second resin layer 32. Examples of additives include antioxidants, slip agents, flame retardants, anti-blocking agents, light stabilizers, dehydrating agents, tackifiers, crystal nucleating agents, etc. These may be used alone or in combination of two or more.
[0087] The first resin layer 31 has a first surface satisfying the following formula (A1) as a surface of the terminal film 16. In formula (A1), from the perspective of being able to suppress the occurrence of electrolyte leakage when dropped and thus further improving the safety of the storage device, a2 / a1 is preferably 0.5 to 4.5, and more preferably 0.8 to 2.5. In formula (A1), a1 is the absorption strength from (B) polyethylene. The same also applies to b1, c1, and d1 in formulas (B1), (C1), and (D1) described later. a2 is the absorption strength from (A) polypropylene. The same also applies to b2, c2, and d2 in formulas (B1), (C1), and (D1) described later.
[0088] 0.3≤a2 / a1≤6.2(A1)
[0089] [In formula (A1), a1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of a2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0090] The second resin layer 32 satisfies the following formula (C1). Thus, the terminal film 16 tends to be able to suppress the occurrence of electrolyte leakage when dropped, thereby further improving the safety of the power storage device. From the same point of view, in the formula (C1), c2 / c1 is preferably 1.5 to 4.0, and more preferably 2.0 to 3.0.
[0091] 1.0≤c2 / c1≤5.8(C1)
[0092] [In formula (C1), c1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of C2 is the wave number 841 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0093] The thickness of the first resin layer 31 and the second resin layer 32 is preferably 10 to 100 μm, and more preferably 15 to 50 μm. When the thickness of the first resin layer 31 and the second resin layer 32 is thinner than 10 μm, the adhesion with the metal terminal 14 may be reduced. In addition, when the thickness of the second resin layer 32 is thicker than 100 μm, it becomes a major factor in increasing the cost of the terminal film 16, which is not preferred.
[0094] The intermediate layer 33 is disposed between the first resin layer 31 and the second resin layer 32. One surface of the intermediate layer 33 is covered by the first resin layer 31, and the other surface is covered by the second resin layer 32. The intermediate layer 33 includes polypropylene. When the intermediate layer 33 includes polypropylene, the film forming property, interlayer adhesion, impact resistance, etc. of the terminal film 16 tend to be excellent.
[0095] The intermediate layer 33 is preferably an insulating layer. The insulating layer is used to prevent the sealant (the sealing layer of the packaging material and the first and second resin layers of the terminal film) from flowing out during heat sealing, and the exposed metal layer of the packaging material from contacting the metal terminal and causing insulation reduction. Therefore, the insulating layer is preferably formed of a resin with a high melting point or glass transition temperature that does not flow out during heat sealing.
[0096] The insulating layer includes polypropylene. As resins other than polypropylene constituting the insulating layer, for example, polyethylene terephthalate, polyethylene naphthalate, polyphenylene sulfide, polymethylpentene, polyacetal, cyclic polyolefin, polyamide, polycarbonate, polyphenylene ether, and polyethylene can be used. As polyethylene and polypropylene, the same materials as those of the first resin layer and the second resin layer can be used. As polypropylene, block polypropylene is preferably used. In addition, when the insulating layer includes polypropylene, the (C) compatibilizer contained in the first resin layer 31 and the second resin layer 32 can not only improve the adhesion with the packaging material, but also improve the adhesion with the insulating layer. The resin constituting the insulating layer can be used alone or in combination of two or more.
[0097] In addition, by adding a pigment to the insulating layer, the insulating layer can be colored. By coloring the insulating layer, the visibility of the terminal film 16 can be improved. As a result, the accuracy of the inspection of the terminal film 16 (specifically, for example, whether the terminal film 16 is attached to the metal terminal 14, the inspection of the installation position of the terminal film 16 relative to the metal terminal 14, etc.) can be improved. Examples of pigments include copper oxide, cobalt oxide, zinc oxide, titanium oxide, carbon black, barium sulfate, quinacridone pigments, polyazo pigments, isoindolinone pigments, etc.
[0098] The intermediate layer 33 satisfies the following formula (B1). Thus, the terminal film 16 tends to be able to suppress the occurrence of electrolyte leakage when dropped, thereby further improving the safety of the power storage device. From the same viewpoint, in the formula (B1), b2 / b1 is preferably 1.5 to 3.0, and more preferably 1.8 to 2.5.
[0099] 1.0≤b2 / b1≤3.2(B1)
[0100] [In formula (B1), b1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of b2 is 841 cm when measured by attenuated total reflection method of infrared spectroscopy. -1 The absorption intensity.]
[0101] The weight average molecular weight of the intermediate layer 33 may be 1.0×10 5 ~5.0×10 6 , preferably 5.0×10 5 ~2.0×10 6 , more preferably 6.0×10 5 ~1.0×10 6 When the weight average molecular weight is 1.0×10 5 When the weight average molecular weight is 5.0×10 6 When the molecular weight is less than 100 μm, the intermediate layer 33 tends to be easy to process. The weight average molecular weight is a value measured by gel permeation chromatography (GPC).
[0102] In addition, the intermediate layer 33 may also be a layer having a structure other than the above-mentioned insulating layer. For example, the intermediate layer 33 may be a layer satisfying one or more of the requirements of a layer containing a resin having a cross-linked structure (cross-linked layer) and a layer containing at least one selected from the group consisting of fillers and fibers (reinforced layer).
[0103] In the crosslinked layer, examples of the resin having a crosslinked structure include crosslinked acrylic resins, epoxy resins, phenolic resins, urea resins, melamine resins, polyurethane resins, etc. These may be used alone or in combination of two or more.
[0104] In the reinforcing layer, as fillers, for example, silica particles, alumina particles, barium sulfate particles, calcium carbonate particles, etc. can be listed. These can be used alone or in combination of two or more. The average particle size of the filler is preferably 0.1 to 10 μm, and the content of the filler is preferably 0.5 to 20 mass % based on the total amount of the reinforcing layer (intermediate layer 33).
[0105] In the reinforcing layer, as the fiber, for example, a fiber composed of a cellulose resin or a resin having a melting point of 200° C. or more used in the heat-resistant layer can be cited. These can be used alone or in combination of two or more. The fiber width of the fiber is preferably 10 nm to 10 μm, and the fiber content is preferably 0.5 to 70% by mass based on the total amount of the reinforcing layer (intermediate layer 33). In addition, the fiber can also be formed into a non-woven fabric.
[0106] The reinforcing layer may be a layer in which the filler and / or fiber is dispersed in the polyolefin resin, a resin having a melting point of 200° C. or higher, a resin having a cross-linked structure, or the like.
[0107] The intermediate layer 33 does not need to be a single-layer structure, and may be a multilayer structure in which a plurality of resin layers are bonded via an adhesive, etc. Therefore, the intermediate layer 33 may be a multilayer structure composed of two or more layers of an insulating layer, a crosslinking layer, and a reinforcing layer.
[0108] The thickness of the intermediate layer 33 (the overall thickness in the case of a multilayer structure) can be appropriately set within a range of 10 to 200 μm, preferably 20 to 100 μm. It should be noted that the balance between the thickness of the intermediate layer 33 and the thickness of the metal terminal 14 and the second resin layer 32 is important. In the case where the thickness of the second resin layer 32 or the metal terminal 14 is thicker, the thickness of the intermediate layer 33 can also be thickened accordingly.
[0109] From the viewpoint of heat sealing, embedding property of metal terminals and insulation, the total thickness of the first resin layer 31, the second resin layer 32 and the intermediate layer 33 (the thickness of the terminal film 16) is preferably 10 to 500 μm, more preferably 15 to 300 μm, and further preferably 30 to 200 μm.
[0110] Regarding the thickness ratio of the first resin layer 31, the intermediate layer 33 and the second resin layer 32 (first resin layer 31: intermediate layer 33: second resin layer 32), when the intermediate layer 33 is an insulating layer, the thickness of the first resin layer 31 and the second resin layer 32 can be made consistent, for example, such as 2:1:2, 1:2:1, 1:1:1, etc. From the perspective of the embeddability of the metal terminal, the thickness of the second resin layer 32 in contact with the metal terminal can be thicker than the thickness of the first resin layer 31, such as 1:1:3, 1:2:2, 3:3:5.
[0111] When the thickness of the first resin layer 31 and the second resin layer 32 are the same, the ratio of their thickness to the thickness of the intermediate layer 33 (first resin layer 31 or second resin layer 32: intermediate layer 33) may be 1:3 to 3:1, or 1:2 to 2:1. When the thickness of the second resin layer 32 is thicker than that of the first resin layer 31, the ratio of the thickness of the second resin layer 32 to the thickness of the intermediate layer 33 (second resin layer 32: intermediate layer 33) may be 4:1 to 1:1, or 3:1 to 1:1, and the ratio of the thickness of the first resin layer 31 to the thickness of the intermediate layer 33 (first resin layer 31: intermediate layer 33) may be 1:3 to 3:1, or 1:2 to 2:1.
[0112] As mentioned above, although the preferred embodiment of the present disclosure has been described in detail, the present disclosure is not limited to the specific embodiment, and various modifications and changes can be made within the scope of the gist of the present disclosure described in the claims.
[0113] For example, in Figure 3 In the description, the terminal film 16 having a three-layer structure is taken as an example, but a second intermediate layer made of an insulating resin or the like may be arranged between the intermediate layer 33 and the first resin layer 31 and between the intermediate layer 33 and the second resin layer 32 .
[0114] In this way, by configuring the second intermediate layer between the intermediate layer 33 and the first resin layer 31, and between the intermediate layer 33 and the second resin layer 32, respectively, to form a multilayer structure of more than four layers, it is possible to improve the insulation between the intermediate layer 33 and the barrier layer 24 (metal layer) constituting the packaging material 13, and the insulation between the intermediate layer 33 and the metal terminal 14. It should be noted that the second intermediate layer may also be the above-mentioned cross-linked layer or reinforcement layer.
[0115] In addition, the terminal film 16 may be composed of one layer or two layers.
[0116] When the terminal film 16 is a single-layer structure, the single layer may have the same structure as the first resin layer 31. In this case, from the viewpoints of heat sealing properties, embedding properties of metal terminals, and insulation properties, the thickness of the first resin layer 31 is preferably 10 to 500 μm, more preferably 15 to 300 μm, and further preferably 30 to 200 μm.
[0117] When the terminal film 16 has a two-layer structure, the side in contact with the packaging material 13 can be the first resin layer, and the side in contact with the metal terminal 14 can be the second resin layer, and at least one layer can be set to the same structure as the first resin layer 31, and the other layer can be set to the same structure as the second resin layer 32 or the intermediate layer 33. In addition, the other layer can also have a different structure from the second resin layer 32 or the intermediate layer 33.
[0118] In addition, the first resin layer 31 and the second resin layer 32 may have the same structure or different structures. The second resin layer 32 may not contain polyethylene. The second resin layer 32 may not satisfy the above formula (C1). The intermediate layer 33 may not contain polyethylene. The intermediate layer 33 may not satisfy the above formula (B1).
[0119] Next, the manufacturing method of the terminal film 16 of the present embodiment is briefly described. There is no particular limitation on the manufacturing method of the terminal film 16. The terminal film 16 can be manufactured using a film extrusion manufacturing device having a mold such as a circular mold used in the inflation molding method or a T mold used in the compression molding method, but from the perspective of film stability, a multi-layer inflation molding method is suitable.
[0120] In the following description, as an example of a method for manufacturing the terminal film 16 , a case where the terminal film 16 is manufactured using an inflation molding method (in other words, an inflation molding device) will be described.
[0121] First, the base materials of the first resin layer 31, the second resin layer 32, and the intermediate layer 33 are prepared. Next, the base materials of the first resin layer 31, the second resin layer 32, and the intermediate layer 33 are supplied to the inflation molding device. Next, while the three base materials are extruded from the extrusion section of the inflation molding device so as to form a three-layer structure (a structure in which the first resin layer 31, the second resin layer 32, and the intermediate layer 33 are stacked), air is supplied from the inside of the laminated body of the extruded three-layer structure.
[0122] Then, the cylindrical terminal film 16 inflated into a cylindrical shape is conveyed, deformed into a flat shape by a guide portion, and then folded into a sheet shape by a pair of pinch rollers. The terminal film 16 in a roll shape is manufactured by cutting the two ends of the folded tube and winding a pair (2 strips) of films in a roll shape onto a winding core.
[0123] The extrusion temperature when manufacturing the terminal film 16 is preferably in the range of 130 to 300° C., more preferably 130 to 250° C. When the extrusion temperature is less than 130° C., the melting of the resin constituting each layer becomes insufficient and the melt viscosity becomes quite large, so the extrusion from the screw may become unstable. On the other hand, when the extrusion temperature exceeds 300° C., the oxidation or degradation of the resin constituting each layer becomes intense, so the quality of the terminal film 16 is reduced.
[0124] The screw rotation speed, inflation ratio, and pulling speed can be appropriately set in consideration of the film thickness. In addition, the film thickness ratio of each layer of the terminal film 16 can be easily adjusted by changing the rotation speed of each screw.
[0125] The terminal film 16 of the present embodiment may be manufactured by dry lamination using an adhesive or a method of laminating formed insulating layers (insulating films) by sandwich lamination.
[0126] Here, refer to Figure 3 , the welding process for melting and bonding the terminal film 16 and the metal terminal 14 of the present embodiment together is described. In the welding process, the terminal film 16 and the metal terminal 14 are thermally welded while the second resin layer 32 is melted by heating and the second resin layer 32 and the metal terminal 14 are closely attached by pressurization.
[0127] In the welding process, heating is performed to a temperature equal to or higher than the melting point of the resin constituting the second resin layer in order to obtain sufficient adhesion and sealing properties between the terminal film 16 and the metal terminal 14 .
[0128] Specifically, the heating temperature of the terminal film 16 may be, for example, 140 to 170° C. The treatment time (the total of the heating time and the pressurizing time) needs to be determined in consideration of the peel strength and productivity. The treatment time may be appropriately set within the range of, for example, 1 to 60 seconds.
[0129] When the production tact (productivity) of the terminal film 16 is prioritized, heat welding may be performed at a temperature exceeding 170° C. and with a shorter pressing time. In this case, the heating temperature may be, for example, 170 to 230° C., and the pressing time may be, for example, 3 to 20 seconds.
[0130] Hereinafter, the present disclosure will be described more specifically based on Examples and Comparisons, but the present disclosure is not limited to the following Examples.
[0131] [Production of terminal film]
[0132] (Example 1)
[0133] The components of the resin layer shown in Table 1 were mixed and dry-blended to prepare a base material of the resin layer. Next, the base material was extruded at a melt temperature of 210° C. using a blown film extrusion manufacturing device (Co-OI type) manufactured by Sumitomo Heavy Industries Modern, Ltd. to form a terminal film consisting of a single resin layer with a thickness of 100 μm.
[0134] (Examples 2 to 26 and Comparative Examples 1 and 2)
[0135] The components of the resin layer and the intermediate layer shown in Tables 1 to 3 are combined and dry-mixed to prepare the base material of the resin layer and the base material of the insulating layer, respectively. Next, the base material of the resin layer (first resin layer), the base material of the insulating layer (intermediate layer), and the base material of the resin layer (second resin layer) are set in a blown film extrusion manufacturing device (Co-OI type) manufactured by Sumitomo Heavy Industries Modern, Ltd., and the above three base materials are extruded using the film extrusion manufacturing device to produce a terminal film with a three-layer structure of the first resin layer / insulating layer / second resin layer. The melting temperature of each base material is set to 210°C. In each embodiment, the thickness of the first resin layer (packaging material side) / insulating layer / second resin layer (lead side) is as follows.
[0136] 20μm / 40μm / 20μm
[0137] In Tables 1 to 3, "PE-butene" means ethylene-ethylene / butene block copolymer, and "PE-butene random" means ethylene-butene random copolymer.
[0138] [Drop test]
[0139] (Examples 2 to 26 and Comparative Examples 1 and 2)
[0140] (1) Production of Tabs
[0141] As the lead, a lead with a width of 5 mm, a length of 30 mm, and a thickness of 100 μm is used. For the material, the positive electrode is set to aluminum and the negative electrode is set to nickel. Both the positive and negative electrodes are subjected to chromium-free surface treatment. As the terminal film, a film cut into a width of 15 mm and a length of 10 mm is used. The terminal film / lead / terminal film are stacked in sequence and welded at a welding temperature of 165°C and a welding time of 10 seconds. In this way, the positive electrode tab and the negative electrode tab are obtained.
[0142] (2) Production of packaging materials
[0143] A laminated body in which PET film (thickness 25 μm) / polyester polyol adhesive (thickness 5 μm) / aluminum foil (thickness 40 μm, A8079-O material) are laminated in sequence is prepared. Both sides of the aluminum foil are subjected to chromium-free surface treatment. Next, the components shown in Tables 1 to 3 are combined and dry-blended to prepare the base material of the sealing layer. Using a T-die extrusion manufacturing device manufactured by Sumitomo Heavy Industries Modern, Ltd., the acid-modified polypropylene (thickness 40 μm) and the base material of the sealing layer (thickness 40 μm) are co-extruded at a melting temperature of 210°C to obtain a packaging material. In the co-extrusion molding, the acid-modified polypropylene is extruded on the surface of the aluminum foil side.
[0144] (3) Battery Pack Manufacturing
[0145] The size of the packaging material is set to 50mm×90mm, folded in half at the long side, and heat-sealed on one side of the 45mm wide side while clamping the positive and negative pole tabs. Heat sealing is performed at 190°C for 5 seconds. The remaining 2 sides without tabs are heat-sealed at 190°C for 3 seconds. First, heat seal the opposite side of the folded back side, then fill with 5g of a mixed solution (dimethyl carbonate: diethyl carbonate: ethylene carbonate = 1:1:1 (weight ratio)), and finally heat seal the opposite side of the tab. In this way, a battery pack for tab evaluation without encapsulating battery elements such as collectors was produced. It should be noted that the production conditions of the above-mentioned battery pack are conditions in which the heating temperature and heat sealing time are more stringent than the conditions of the actual battery production process.
[0146] (4) Safety evaluation
[0147] The battery pack was dropped from a height of 3 m at room temperature. The battery pack after the drop was checked for leakage of liquid. 50 battery packs were evaluated under the same conditions and according to the following evaluation criteria. The results are shown in Tables 1 to 3.
[0148] A: The number of leaking battery packs is less than 2
[0149] B: The number of leaking battery packs is more than 3 but less than 5
[0150] C: The number of leaking battery packs is more than 6 and less than 9
[0151] D: The number of leaking battery packs is more than 10
[0152] [Measurement of absorption intensity based on infrared spectroscopy]
[0153] <First Resin Layer>
[0154] (Example 1)
[0155] The terminal film was cut to obtain a measurement sample (size: 20 mm×20 mm). The absorption intensity of the infrared absorption spectrum (wave number 720 cm) was measured for the outermost surface of the measurement sample using the attenuated total reflection measurement method (ATR) of Fourier transform infrared (FT-IR) spectroscopy. -1 and 841cm -1 ). The measuring apparatus and conditions are as follows. Based on the measuring results, (a2 / a1) in the above formula (A1) was calculated. The results are shown in Tables 1 to 3.
[0156] {Measurement Apparatus and Conditions}
[0157] Measuring device: Spectrum Spotlight 400 (trade name, manufactured by PerkinElmer)
[0158] Prism: Germanium
[0159] Wave number resolution: 4cm -1
[0160] Total times: 4 times
[0161] Baseline: wave number 2000~2300cm -1 The average transmittance between
[0162] Wave number 720cm -1 and 841cm -1 Absorption intensity: above baseline and wave number 720cm -1 and 841cm -1 The difference in transmittance
[0163] (Examples 2 to 26 and Comparative Examples 1 and 2)
[0164] A measurement sample was obtained in the same manner as in Example 1. The absorption intensity of the infrared absorption spectrum was measured on the outermost surface of the first resin layer side of the measurement sample in the same manner as in Example 1. (a2 / a1) in the above formula (A1) was calculated from the measurement results. The results are shown in Tables 1 to 3.
[0165] <Middle Layer>
[0166] (Examples 2 to 26 and Comparative Examples 1 and 2)
[0167] The sample for measurement was obtained in the same manner as the measurement of the absorption intensity of the first resin layer. In addition, the sample was cut from the surface layer to the surface layer on the opposite side using a microtome to expose the intermediate layer. The absorption intensity of the infrared absorption spectrum of the intermediate layer was measured using micro ATR. The measuring apparatus and conditions were the same as those for the measurement of the first resin layer. Based on the measurement results, (b2 / b1) in the above formula (B1) was calculated. The results are shown in Tables 1 to 3.
[0168] <Second Resin Layer>
[0169] (Examples 2 to 26 and Comparative Examples 1 and 2)
[0170] The sample for measurement was obtained in the same manner as the measurement of the absorption intensity of the first resin layer. The absorption intensity of the infrared absorption spectrum of the outermost surface of the second resin layer side of the sample for measurement was measured. The measuring apparatus and conditions were the same as those for the measurement of the first resin layer. Based on the measurement results, (c2 / c1) in the above formula (C1) was calculated. The results are shown in Tables 1 to 3.
[0171] <Sealing layer>
[0172] (Examples 1 to 26 and Comparative Examples 1 and 2)
[0173] The packaging material was prepared in the same manner as in "(2) Preparation of packaging material" of the above drop test. The packaging material was cut to obtain a sample for measurement (size: 20 mm×20 mm). The absorption intensity of the infrared absorption spectrum of the outermost surface of the sealing layer of the sample for measurement was measured. The measuring apparatus and conditions were the same as those for the measurement of the first resin layer. Based on the measurement results, (d2 / d1) in the above formula (D1) was calculated. The results are shown in Tables 1 to 3.
[0174] [Table 1]
[0175]
[0176] [Table 2]
[0177]
[0178] [Table 3]
[0179]
[0180] The gist of the present disclosure lies in the following [1] to [9].
[0181] [1] A terminal film for an electric storage device, which is used to cover a portion of the outer peripheral surface of a metal terminal constituting the electric storage device,
[0182] Contains polypropylene and polyethylene,
[0183] The terminal film has a first surface satisfying the following formula (A1).
[0184] 0.3≤a2 / a1≤6.2(A1)
[0185] [In formula (A1), a1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of a2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0186] [2] The terminal film for a power storage device according to [1], further comprising a compatibilizer having a portion compatible with the polypropylene and a portion compatible with the polyethylene.
[0187] [3] The terminal film for a power storage device according to [2], wherein the compatibilizer is a block copolymer or a graft copolymer.
[0188] [4] A terminal film for an electric storage device, which is used to cover a portion of the outer peripheral surface of a metal terminal constituting the electric storage device, comprising:
[0189] a first resin layer comprising polypropylene and polyethylene,
[0190] a second resin layer comprising polypropylene, and
[0191] an intermediate layer provided between the first resin layer and the second resin layer and comprising polypropylene,
[0192] The first resin layer has a first surface satisfying the following formula (A1) as one surface of the terminal film.
[0193] 0.3≤a2 / a1≤6.2(A1)
[0194] [In formula (A1), a1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of a2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0195] [5] The terminal film for a power storage device according to [4], wherein the intermediate layer satisfies the following formula (B1).
[0196] 1.0≤b2 / b1≤3.2(B1)
[0197] [In formula (B1), b1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of b2 is 841 cm when measured by attenuated total reflection method of infrared spectroscopy. -1 The absorption intensity.]
[0198] [6] The terminal film for a power storage device according to [4] or [5], wherein the second resin layer satisfies the following formula (C1).
[0199] 1.0≤c2 / c1≤5.8(C1)
[0200] [In formula (C1), c1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of C2 is the wave number 841 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0201] [7] The terminal film for a power storage device according to any one of [4] to [6], wherein the first resin layer contains a compatibilizer having a portion compatible with the polypropylene and a portion compatible with the polyethylene.
[0202] [8] The terminal film for a power storage device according to [7], wherein the compatibilizer is a block copolymer or a graft copolymer.
[0203] [9] An electric storage device comprising:
[0204] Power storage device body,
[0205] a metal terminal electrically connected to the power storage device body,
[0206] a packaging material that holds the metal terminal and accommodates the power storage device body, and
[0207] The terminal film for a power storage device according to any one of [1] to [7] covers a portion of the outer peripheral surface of the metal terminal and is arranged between the metal terminal and the packaging material.
[0208] The packaging material has a sealing layer containing polypropylene,
[0209] The terminal film is arranged in such a manner that the first surface contacts the sealing layer,
[0210] The sealing layer satisfies the following formula (D1).
[0211] 0.8≤d2 / d1≤8.5(D1)
[0212] [In formula (D1), d1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy -1 The absorption intensity of d2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity.]
[0213] Explanation of symbols
[0214] 10 ... power storage device, 13 ... packaging material, 14 ... metal terminal (tab lead), 21 ... sealing layer, 31, 32 ... resin layer, 33 ... intermediate layer.
Claims
1. A terminal film for an electric storage device, which is used to cover a part of the outer peripheral surface of a metal terminal constituting the electric storage device, Contains polypropylene and polyethylene, The terminal film has a first surface satisfying the following formula (A1), 0.3≤a2 / a1≤6.2(A1) In formula (A1), a1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity of a2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 absorption intensity. 2 . The terminal film for a power storage device according to claim 1 , comprising a compatibilizer having a portion compatible with the polypropylene and a portion compatible with the polyethylene.
3. The terminal film for a power storage device according to claim 2, wherein: The compatibilizer is a block copolymer or a graft copolymer.
4. A terminal film for an electric storage device, which is used to cover a portion of the outer peripheral surface of a metal terminal constituting the electric storage device, comprising: a first resin layer comprising polypropylene and polyethylene, a second resin layer comprising polypropylene, and an intermediate layer provided between the first resin layer and the second resin layer and comprising polypropylene, The first resin layer has a first surface satisfying the following formula (A1) as one surface of the terminal film, 0.3≤a2 / a1≤6.2(A1) In formula (A1), a1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity of a2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 absorption intensity.
5. The terminal film for a power storage device according to claim 4, wherein The intermediate layer satisfies the following formula (B1), 1.0≤b2 / b1≤3.2(B1) In formula (B1), b1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity of b2 is 841 cm when measured by attenuated total reflection method of infrared spectroscopy. -1 absorption intensity.
6. The terminal film for a power storage device according to claim 4 or 5, wherein The second resin layer satisfies the following formula (C1): 1.0≤c2 / c1≤5.8(C1) In formula (C1), c1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity of C2 is the wave number 841 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 absorption intensity.
7. The terminal film for a power storage device according to any one of claims 4 to 6, wherein The first resin layer includes a compatibilizer having a portion compatible with the polypropylene and a portion compatible with the polyethylene.
8. The terminal film for a power storage device according to claim 7, wherein The compatibilizer is a block copolymer or a graft copolymer.
9. An electric storage device comprising: Power storage device body, a metal terminal electrically connected to the power storage device body, a packaging material that holds the metal terminal and accommodates the power storage device body, and The terminal film for a power storage device according to any one of claims 1 to 8 covers a portion of the outer peripheral surface of the metal terminal and is arranged between the metal terminal and the packaging material, The packaging material has a sealing layer containing polypropylene, The terminal film is arranged in such a manner that the first surface contacts the sealing layer, The sealing layer satisfies the following formula (D1): 0.8≤d2 / d1≤8.5(D1) In formula (D1), d1 represents the wave number 720 cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 The absorption intensity of d2 is the wave number 841cm when measured by attenuated total reflection measurement method of infrared spectroscopy. -1 absorption intensity.
Citation Information
Patent Citations
Adhesive film for metal terminal, method for manufacturing adhesive film for metal terminal, metal terminal with adhesive film for metal terminal, electricity storage device using said adhesive film for metal terminal, and method for manufacturing electricity storage device
JP2022008803A